Neoliberal security provision: Between state practices and individual experience - Hörnqvist, Magnus (Punishment & society, 2020)
The article develops a new understanding of neoliberal security provision on the basis of available accounts of three different “states”; the penal state, the regulatory state, and the activating welfare state. I argue that these forms of state intervention provide individuals with security in the sense that anxiety is temporarily alleviated, while stabilizing the conflictual dynamic of global power structures. Marketization and organizational control account for the specifically neoliberal character. Such an understanding matters because it directs attention to the dynamic between state practices and individual experience, and the multitude of mechanisms, which not only promise but also provide security, however temporary and partial.